Erythema gyratum repens associated with diffuse b-cell lymphoma-report of a rare case - Angoori Gnaneshwar Rao; Syeda Saba Farheen; Kolli Amit; Uday Deshmukh Reddy; Karanam Aparna; Javadevapuram Kranthi; Ruhi Hukkani (Wolters Kluwer Medknow Publications, 2019)
Erythema gyratum repens (EGR) is a rare paraneoplastic dermatosis known to be associated with internal malignancy. Herein, we report a case of EGR with diffuse large B-cell lymphoma (DLBCL) in a young farmer who presented with generalized massive lymphadenopathy and wood-grain pattern dermatosis. Lymph node biopsy with immunohistochemistry established the diagnosis of DLBCL. He was managed by the oncologist with R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone) regimen which alleviated his symptoms considerably after completion of three cycles and was under follow-up.